Edukasi Anti-Bullying pada Siswa Sekolah Dasar Negeri Tawar, Kecamatan Gondang, Kabupaten Mojokerto (Jurnal Pelayanan Masyarakat, 2026)
Bullying remains a serious issue in elementary schools, affecting children’s psychological, social, and academic well-being. Limited student understanding of the forms and impacts of bullying encouraged students of the Community Service Program (KKN) from Mayjen Sungkono University to implement an anti-bullying education program at Tawar State Elementary School. This activity aimed to enhance students’ understanding of bullying while fostering empathy and care toward peers. The program employed an educative–participatory approach through presentations, interactive discussions, question-and-answer sessions, and ice-breaking activities tailored to the characteristics of elementary school students. The participants consisted of 39 students from grades 4 and 5. Evaluation was conducted through observations of student participation, enthusiasm, and their ability to answer questions related to the delivered material. The results indicated that most students were able to understand the concept of bullying, its types, negative impacts, and prevention strategies. Furthermore, students began to apply anti-bullying values in their daily social interactions within the school environment. Anti-bullying education is expected to serve as a preventive measure in creating a safe, comfortable, and supportive school environment that optimally supports students’ growth and development.